Analisis Strategi Pemasaran Usaha Peternakan Ayam Petelur di Kecamatan Mungka (Studi Kasus Peternakan Bersama Farm Kecamatan Mungka Kabupaten Lima Puluh Kota) - Fauzan Rifqi; Tiara Turay (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
The laying hen farming sector is increasingly challenged by intense market competition, fluctuating production input prices, and limitations in marketing access, which may adversely affect sales performance and business sustainability. Consequently, the formulation of an effective marketing strategy is essential to improve competitiveness and increase sales turnover. This study employed a qualitative descriptive approach using purposive sampling to determine the research sample. Data were collected through structured interviews and questionnaires and subsequently analyzed using SWOT analysis and the marketing mix framework. The objective of this study was to analyze the marketing strategies of the laying hen farming business in increasing sales turnover and to identify the obstacles and constraints encountered by Bersama Farm in developing its business in Mungka District, Lima Puluh Kota Regency. The results indicate that Bersama Farm obtained an Internal Factor Evaluation (IFE) score of 3.546 and an External Factor Evaluation (EFE) score of 3.152. Based on the results of the IFE, EFE, Internal–External (IE), and SWOT analyses, Bersama Farm is positioned in Quadrant I, which represents a growth and build strategic position. This position reflects strong internal capabilities and favorable external opportunities that support business expansion. Therefore, the recommended strategies include intensive strategies such as market penetration, market development, and product development, as well as integration strategies encompassing backward integration, forward integration, and horizontal integration. The findings imply that the implementation of a more aggressive and structured marketing strategy, supported by product innovation, business diversification, and stakeholder collaboration, is crucial to ensure sustainable growth and enhanced competitiveness in the laying hen farming industry